Rape and Mental Health Outcomes Among Women: Examining the Moderating Effects of "Healthy" Fear Levels. (August 2017) - Spohn, Ryan; Wright, Emily M.; Peterson, Johanna C.
This study examined the mediating and moderating impact of fear of victimization on the relationships between forcible and vicarious rape on depression and post-traumatic stress disorder (PTSD) among college women. Forcible and vicarious rape positively affected PTSD and depression symptomology, but fear did not mediate these relationships. Fear moderated the impact of forcible rape on PTSD, but was not a moderator for depression. Findings suggest that there may be "healthy" levels of fear in the aftermath of victimization where having too little fear may leave women unnecessarily vulnerable to victimization, while having too much fear may lead to social isolation and withdrawal.